LRIG3 Suppresses Angiogenesis by Regulating the PI3K/AKT/VEGFA Signaling Pathway in Glioma - Peng, Chenghao; Chen, Hanmin; Li, Youwei; Yang, Hang; Qin, Peizhong; Ma, Baojun; Duan, Qiuhong; Wang, Baofeng; Mao, Feng; Guo, Dongsheng (Frontiers in Oncology, 2021)
High levels of microvessel density (MVD) indicate poor prognosis in patients with malignant glioma. Leucine-rich repeats and immunoglobulin-like domains (LRIG) 3, a potential tumor suppressor, plays an important role in tumor progression and may serve as a biomarker in many human cancers. However, its role and underlying mechanism of action in glioma angiogenesis remain unclear. In the present study, we used loss- and gain-of-function assays to show that LRIG3 significantly suppressed glioma-induced angiogenesis, both in vitro and in vivo. Mechanistically, LRIG3 inhibited activation of the PI3K/AKT signaling pathway, downregulating vascular endothelial growth factor A (VEGFA) in glioma cells, thereby inhibiting angiogenesis. Notably, LRIG3 had a significant negative correlation with VEGFA expression in glioma tissues. Taken together, our results suggest that LRIG3 is a novel regulator of glioma angiogenesis and may be a promising option for developing anti-angiogenic therapy.